Konvergensi Radio dalam Mempertahankan Eksistensi di Era Digital dan Covid-19 - Khasna’ Lathifah; Ismandianto Ismandianto (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2021)
Media convergence is a step to maintain existence amid the many emerging new media. The innovations carry out have increasingly developed since the Covid-19 virus pandemic. This study aimed to see the existence of RRI Pekanbaru after conduct media convergence and to see the impact of media convergence felt by both internally and listeners of RRI Pekanbaru. This study used a descriptive qualitative method and strength by Roger Fidler's concept of Mediamorfosis. This study showed that there was not much audience or audience segmentation because audiences were looking for information or entertainment through social media. The step taken by RRI Pekanbaru to maintain its existence in the digital era is to keep abreast of technological developments, especially during the Covid era. The convergence that brings creates an increasingly interactive character capable of obtaining direct consequences for the message conveyed.